Modern C++ programming cookbook master modern C++ including the latest features of C++23 with 140+ practical recipes - Bancila, Marius (Expert insight, 2024)
The updated third edition of Modern C++ Programming Cookbook addresses the latest features of C++23, such as the stack library, the expected and mdspan types, span buffers, formatting library improvements, and updates to the ranges library. It also gets into more C++20 topics not previously covered, such as sync output streams and source_location. The book is organized in the form of practical recipes covering a wide range of real-world problems. It gets into the details of all the core concepts of modern C++ programming, such as functions and classes, iterators and algorithms, streams and the file system, threading and concurrency, smart pointers and move semantics, and many others. You will cover the performance aspects of programming in depth, and learning to write fast and lean code with the help of best practices. You will explore useful patterns and the implementation of many idioms, including pimpl, named parameter, attorney-client, and the factory pattern. A chapter dedicated to unit testing introduces you to three of the most widely used libraries for C++: Boost.Test, Google Test, and Catch2. By the end of this modern C++ programming book, you will be able to effectively leverage the features and techniques of C++11/14/17/20/23 programming to enhance the performance, scalability, and efficiency of your applications.